The impact of US LNG exports on global markets - Rogers, H (Oxford Institute for Energy Studies, 2015)
Despite its relative maturity as a gas producing province, the USA has defied the expectations of market participants and observers over the past two decades. Figure 9.1 shows the make-up of supply to the US market comprising: US gas production, Canadian pipeline imports (net), net LNG imports, and pipeline exports to Mexico (net).